The contribution of cell-cell signaling and motility to bacterial biofilm formation - Shrout, Joshua D. (2011)
Many bacteria grow attached to a surface as biofilms. Several factors dictate biofilm formation, including responses by the colonizing bacteria to their environment. Here we review how bacteria use cell-cell signaling (also called quorum sensing) and motility during biofilm formation. Specifically, we describe quorum sensing and surface motility exhibited by the bacterium Pseudomonas aeruginosa, a ubiquitous environmental organism that acts as an opportunistic human pathogen in immunocompromised individuals. P. aeruginosa uses acyl-homoserine lactone signals during quorum sensing to synchronize gene expression important to the production of polysaccharides, rhamnolipid, and other virulence factors. Surface motility affects the assembly and architecture of biofilms, and some aspects of motility are also influenced by quorum sensing. While some genes and their function are specific to P. aeruginosa, many aspects of biofilm development can be used as a model system to understand how bacteria differentially colonize surfaces.